Costs of Potential Medication Wastage Due to Switching Treatment Among People With Multiple Sclerosis - Darin T. Okuda; Achal Patel; Robert Schuldt; Ibraheem Abioye; Nicole G. Bonine (Journal of Health Economics and Outcomes Research)
**Background:** Unused medications negatively impact healthcare resource utilization and environmental safety, contribute substantially to annual healthcare expenditures, and may ultimately affect patient health outcomes. People with multiple sclerosis (PwMS) commonly switch disease-modifying therapies (DMTs), leading to medication wastage and substantial costs for insurers and patients.